2001
DOI: 10.2307/3079189
|View full text |Cite
|
Sign up to set email alerts
|

The Strength of Phenotypic Selection in Natural Populations

Abstract: How strong is phenotypic selection on quantitative traits in the wild? We reviewed the literature from 1984 through 1997 for studies that estimated the strength of linear and quadratic selection in terms of standardized selection gradients or differentials on natural variation in quantitative traits for field populations. We tabulated 63 published studies of 62 species that reported over 2,500 estimates of linear or quadratic selection. More than 80% of the estimates were for morphological traits; there is ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
1,199
28
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(1,312 citation statements)
references
References 0 publications
84
1,199
28
1
Order By: Relevance
“…Selection gradients and differentials are popular comparative measures for studying natural selection for phenotypes (Kingsolver et al 2001). Another metric for the strength of selection is the opportunity for selection, often identified by I , defined as the variation in relative fitness among individuals in a population (or the mean-standardized variance - Crow 1958, O’Donald 1970, Wade 1979, Wade and Arnold 1980).…”
Section: Applicationsmentioning
confidence: 99%
“…Selection gradients and differentials are popular comparative measures for studying natural selection for phenotypes (Kingsolver et al 2001). Another metric for the strength of selection is the opportunity for selection, often identified by I , defined as the variation in relative fitness among individuals in a population (or the mean-standardized variance - Crow 1958, O’Donald 1970, Wade 1979, Wade and Arnold 1980).…”
Section: Applicationsmentioning
confidence: 99%
“…This lack of knowledge results partly from the extreme difficulty of measuring the strength and describing the pattern of selection acting in natural populations (Kingsolver et al, 2001). This problem is particularly acute in studies of fishes, where estimates of fitness components (among them survival) in wild populations are notoriously difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews of the published literature have addressed this question. Kingsolver et al (2001) concluded that directional selection was typically weak, although the frequency distribution of selection gradients displayed a long right tail, indicating that selection was sometimes strong. In contrast, Hereford et al (2004) concluded that selection in nature was typically strong.…”
Section: Discussionmentioning
confidence: 99%
“…They calculated univariate variance-standardized selection gradients (which they called i , although what they calculated is the same as what Kingsolver et al [2001] call β and Hereford et al [2004] call β σ ) for selection acting through reproduction. Values across three years ranged from −0.26 standard deviation units to +0.08 standard deviation units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation